Intermetallic Compounds in Al‐SUS316L Composites. Issue 10 (16th August 2018) - Park, Kwangjae; Kim, Dasom; Park, Jehong; Cho, Seungchan; Takamichi, Miyazaki; Kwon, Hansang
Abstract : Aluminum (Al)‐stainless steel 316L (SUS316L) composites are successfully manufactured by spark plasma sintering (SPS) using pure Al and SUS316L powders as the raw materials. The Al‐SUS316L composite powder is prepared from a 1:1 mixture by volume of Al and SUS316L by mechanical ball milling. This composite powder is subjected to SPS at four different temperatures (500, 550, 600, and 630 °C) at a pressure of 200 MPa and held at the desired temperature for 5 min. Intermetallic compounds such as AlFe3 and Al13 Fe4, which are detected based on their X‐ray diffraction (XRD) patterns, are created in the Al‐SUS316L composites during SPS. In addition, scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS), field emission‐electron probe microanalysis (FE‐EPMA), and thermogravimetric and differential thermal analysis (TG‐DTA) also confirm the formation of intermetallic compounds. Moreover, the authors conduct a detailed analysis of the intermetallic compounds using transmission electron microscopy (TEM). The intermetallic compounds are well dispersed in Al‐SUS316L composites and the layer of these becomes thicker as the sintering temperature increases to 630 °C. Moreover, the intermetallic compounds can help to make a strong chemical bonding between Al and SUS316L matrix. Consequently, the Al‐SUS316L composites manufactured by the SPS process can be applied in engineering industries such as the automobile, aerospace, and construction industries as high‐strength and lightweight materials. Abstract : Aluminum(Al)‐stainless steel316L(SUS316L) composites are successfully manufactured by spark plasma sintering (SPS) using pure Al and SUS316L powders. Intermetallic compounds such as AlFe3 and Al13 Fe4 are created in the Al‐SUS316L composites during SPS. The Al‐SUS316L composites manufactured by the SPS can be applied in engineering industries such as the automobile manufacturing, ocean engineering and ship building as lightweight and high‐corrosion‐resistance materials.